RADI-12. CORRELATION BETWEEN F-DOPA PET AND MRI IN BRAIN TUMOURS. Issue 2 (22nd June 2018) - Fraioli, Francesco; Shankar, Ananth; Hyare, Harpreet; Rega, Marilena; Mankad, Kshitij; Militano, Vincenzo; Voo, Stefan; Ferrazzoli, Valentina; Barnes, Anna
Abstract: We assessed DOPA PET for staging (5) or progression (10) in adolescent patients (age 17 ± 4) with brain tumour in comparison with contrast MRI. 15 patients underwent 18 DOPA PET/MRI (2 had repeated follow up) (2 germinoma and 13 gliomas, 7 high grade [HGG] and 6 low grade glioma[LGG]). Two NM physicians recorded quantitative PET parameters. Two neuroradiologists recorded tumour characteristics. The Gold Standard was either surgery or clinical follow-up. The readers drew the volume of tumour on a dedicated platform (ITK-SNAP) on PET or on MR. The association of PET and MRI parameters was evaluated by non-parametric correlation analysis. Intermodality variability on the PET and MRI volumes, their ratios and percentage of overlapping were assessed. 16 lesions were established as tumour persistence/recurrence by histological and clinical criteria. Three LGG and 1 HGG were positive on MR and negative on PET, all non-enhancing on post contrast MR. GS demonstrated disease. With a cut-off value of SUVmax 2.20, TBR 1.30 and TSR 0.90, a sensitivity of 87% was achieved in tumour assessment/ progression on DOPA PET. In most of the patients there was excellent overlapping between PET and MRI volumes (average 59%). In 3 patients there were mismatch of volumes (0 to 23%) with different areas of uptake/enhancement in the 2 modalities. Our preliminary results showed that DOPA PET is accurate for primary assessment/recurrence. In few cases there was a volume mismatch on uptake/enhancement/signal change, which might reflect different biological behaviors of the tumours.